Development of automatic control system of motion of an unmanned surface ships with a sailing installation - Nadtochii, Victor; Nadtochiy, Anatoly; Bugrim, Leonid (Technology audit and production reserves, 2019)
The object of research is an unmanned surface ship with a sailing installation. One of the problems in controlling a sailing ship using automatic systems is the almost infinite number of static and dynamic states of traditional sails, which are difficult to detect and difficult to predict. In addition, the ability of traditional sails to twist and engage is known, and all operations with sails are performed through the operation of a running and standing rigging, that is, indirectly. Given the need for continuous deployment and cleaning of conventional sails, building an automatic control system for them will obviously be an extremely difficult task. The paper considers an alternative to the traditional sail – a rigid sail-wing. For unmanned surface ships, the sail-wing is proposed to be made on the basis of symmetrical aerodynamic profiles. Such a sail-wing will simplify such a procedure as cleaning the sail, that is, ensuring its inactivity, as well as simplify the procedure for the transition of a sailing ship by moving the right or left tacks. The study presents relatively simple control algorithms that are possible when using symmetrical aerodynamic profiles for rigid sails. Such sails will make it relatively easy to implement the modes of motion of unmanned ships with tacks, as well as the mode of inactivity of the sail. Also shown is the need to build a system that combines the functions of controlling the angle of attack of the wing-sail and course control. In this case, the control system of the angle of attack does not depend on the heading control system, and the heading control system must take into account the sailing mode. Overcoming the critical transition points of the ship from one tack to another is possible using an additional propulsion device. The control of the sail-wing can be carried out using one single electric drive returns it relative to the wind at a given angle of attack, which ensures its driving force.